Indonesian Civil Service Management in the Health and Disaster Management Sector: Post-COVID-19 Pandemic Prospective - Syah, Robby Firman; Rachman, Nisa Agistiani; Gusparirin, Rori; Simandjorang, Bonataon Maruli Timothy Vincent; Mudrawan, Indra; Suwarno, Yogi (Jurnal Borneo Administrator, 2024)
The COVID-19 pandemic as a non-natural disaster has made many countries aware of reform in healthcare systems and services and disaster management, including Indonesia. The high intensity of natural disasters in Indonesia and the presence of non-natural disasters such as the COVID-19 pandemic have become the government's momentum to carry out better mitigation in the future. This study aims to identify and analyse the gap between the existing conditions and the ideal conditions for the needs of the State Civil Apparatus (ASN) in the health and disaster management sector in the future. Using a gap analysis approach with qualitative data collection, this study shows a significant gap between the availability of ASN compared to the number of ASN needed in the health and disaster management sectors in Indonesia. Moreover, to make the health and disaster management sector successful, this study formulates the need for ASNs in strategic positions: Specialist Doctor, General Practitioner, Dentist, Pharmacy and Food Supervisor, and Rescuer. In addition, this study suggests the need for developing ASN competencies in this sector, such as digital services, biotechnology, nanotechnology, integrated flood management, construction of drinking water supply systems and landfills, risk management, and review analysis and mitigation